To find the solution to the system of equations represented by the given table, we need to look for the values of \(x\) and \(y\) that satisfy both equations simultaneously.
The two equations are:
- \(y = 2x - 5\)
- \(y = x - 3\)
Let's check the given \( (x, y) \) pairs from the table:
-
\( (0, -5) \)
- For \(y = 2(0) - 5 = -5\) and \(y = 0 - 3 = -3\): No solution.
-
\( (1, -3) \)
- For \(y = 2(1) - 5 = -3\) and \(y = 1 - 3 = -2\): No solution.
-
\( (2, -1) \)
- For \(y = 2(2) - 5 = -1\) and \(y = 2 - 3 = -1\): Both equate to -1. This is a solution.
-
\( (3, 1) \)
- For \(y = 2(3) - 5 = 1\) and \(y = 3 - 3 = 0\): No solution.
-
\( (3, 0) \): This pair was not in the table, but based on the evaluation above, only \( (2, -1) \) matches both equations.
Given that only \( (2, -1) \) satisfies both equations, the correct response from the available options is:
(2,−1)